2012
DOI: 10.1016/j.jcrs.2011.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of traumatic LASIK flap dislocation with macrostriae and epithelial ingrowth 14 years postoperatively

Abstract: Fourteen years after uneventful laser in situ keratomileusis (LASIK), a 59-year-old woman presented after suffering blunt trauma to her left eye 5 weeks earlier. The injury resulted in traumatic flap dislocation, epithelial ingrowth, and significant macrostriae. Following epithelial removal, the flap was hydrated with sterile water, facilitating reduction of the macrostriae and reapproximation without the need for suture placement. The postoperative course was uneventful, and at 1 month, the epithelial ingrowt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 40 publications
0
31
0
1
Order By: Relevance
“…Due to the inability to fully unfold the flap and also due to the presence of a partial tissue defect, they had to use three stiches of interrupted 11-0 nylon sutures to secure the flap and to prevent the recurrent ingrowth of epithelium. Holt et al (2012) reported repair of a mild flap dislocation after a delay of one month. While the flap had macrostriae, it did not have extensive folds and was successfully repositioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the inability to fully unfold the flap and also due to the presence of a partial tissue defect, they had to use three stiches of interrupted 11-0 nylon sutures to secure the flap and to prevent the recurrent ingrowth of epithelium. Holt et al (2012) reported repair of a mild flap dislocation after a delay of one month. While the flap had macrostriae, it did not have extensive folds and was successfully repositioned.…”
Section: Discussionmentioning
confidence: 99%
“…However, a drawback of LASIK that can occur is poor wound healing between the flap and the stromal bed (Dawson et al, 2005). Even 10 years or more after LASIK surgery, an inadvertent blunt trauma can cause dislocation of the flap (Holt et al, 2012). Commonly, traumatic dislocation of the post-LASIK flap is an emergency and needs a surgeon to reposition the flap, the sooner the better (Melki et al, 2000;Landau et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Two cases did not require debridement of epithelial ingrowth; one case in the series involving corneal perforation mandated penetrating keratoplasty. Our case is the latest-onset of traumatic epithelial ingrowth, 15 years after initial LASIK, and the only case without flap displacement [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]20]. …”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for epithelial ingrowth include multiple LASIK procedures and hyperopic correction as opposed to myopic correction [4]. Case reports of traumatic incidents that have disrupted the corneal flap have also been reported, inducing epithelial ingrowth and, in one case, ingrowth was delayed 14 years after initial LASIK [5]. There are no reports of epithelial ingrowth after LASIK without corneal flap displacement.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Late flap dislocation from trauma occurring several years after LASIK has also been reported. 5,6 We describe 2 cases involving a partial portion of the LASIK flap that was torn and flipped anteriorly or posteriorly relative to the intact portion of the remaining flap. The tears occurred years after LASIK and remained fixed for months.…”
mentioning
confidence: 99%